(untitled) (Swiss Medical Weekly, 2012)
Systemic-onset juvenile idiopathic arthritis (SoJIA), sometimes called Still’s disease, is a systemic inflammatory disease classified within the spectrum of juvenile idiopathic arthritis (JIA). It is an orphan disease with often a chronic course and a major impact on the affected children and their families. This disorder is unique in terms of clinical manifestations, prognosis and response to conventional immunosuppressants. The objectives of this review are to describe SoJIA and emphasise the recent advances in the pathogenesis and treatment, which have transformed the care and the prognosis of this potentially life-threatening paediatric condition.